All Days 2002
DOI: 10.4043/14310-ms
|View full text |Cite
|
Sign up to set email alerts
|

Double Catenary Offloading Lines for Deepwater Fields

Abstract: The use of non-weathervaning floating production units is found feasible for fields in the deep waters of West Africa. The lack of pipeline infrastructure in these remote areas requires export of produced fluid from an offloading system. The transfer of product from the production vessel to offloading buoy is carried out by large diameter suspended flexible flow-lines. The flow-lines are configured in a double wave shape, "W" concept, by introducing distributed buoyancy along the middle section of the lines.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, for practical OOL structures in FPSO offloading systems, related fatigue analysis and design optimization research are insufficient. Chaudhury [8] proposed a "U"-type oil pipeline and made a comparative analysis of the "U"-type oil pipeline and the "W"-type oil pipeline, including strength characteristics, fatigue characteristics, economic advantages, etc. Through this research, it was found that the "U"-type oil pipeline is superior to the "W"-type oil pipeline in fatigue behavior.…”
Section: Introductionmentioning
confidence: 99%
“…However, for practical OOL structures in FPSO offloading systems, related fatigue analysis and design optimization research are insufficient. Chaudhury [8] proposed a "U"-type oil pipeline and made a comparative analysis of the "U"-type oil pipeline and the "W"-type oil pipeline, including strength characteristics, fatigue characteristics, economic advantages, etc. Through this research, it was found that the "U"-type oil pipeline is superior to the "W"-type oil pipeline in fatigue behavior.…”
Section: Introductionmentioning
confidence: 99%